Labour income inequality in Mexico: Puzzles solved and unsolved - Raymundo M. Campos-Vazquez; Nora Lustig (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We analyse the evolution and proximate determinants of labour income inequality in Mexico between 1989 and 2017. Labour income inequality increased between 1989 and 1994 and declined between 1994 and 2006. What happened after 2006 is subject to uncertainty. The national labour force survey shows a steady decline and the income expenditure survey suggests that inequality increased. We correct for high and rising item (labour income) non-response and under-representation of high-wage earners through a 'hot deck' imputation method and post-survey weight adjustments. We obtain the new weights for formal workers from tabulations recently released by the Mexican social security administration. For informal workers, we correct using the hot deck imputation method. With corrected data, inequality no longer declines between 2006 and 2017.
Keywords: D31; D63; I24; J31; O54; 330; inequality; labour income; post-survey reweighting; imputation; decomposition methods; Mexico